Relearning Old Lessons for the Future of Food-By Bread Alone No Longer: Diversifying Diets with Fruit and Vegetables - Keatinge, John D.H.; Waliyar, Farid; Jamnadas, Ramni H.; Moustafa, Ahmed; Andrade, Maria; Drechsel, Pay; Hughes, Jacqueline d'Arros; Kadirvel, Palchamy; Luther, Kartini (Wiley, 2010)
Diversifying diets and agricultural enterprises with fruit and vegetables is a potent weapon in the current global battle against malnutrition and poverty. Agricultural science can contribute substantially to enhance the development prospects and health of not only disadvantaged and vulnerable individuals at one end of the spectrum but also the growth and equity of national economies at the other. Moreover, with relatively simple applied research, new crop species and technologies can rapidly enter the development pathway to benefit even the poorest people or nations. More upstream research can help to guard fruit and vegetable production against the vagaries of potential climatic uncertainty, which is projected to become more prominent over future decades. However, historical and continuing widespread underinvestment in fruit and vegetable research and development from the national to the global level may severely compromise the world's ability to use such high‐value species for crop diversification and as a major engine of development growth to ensure global food and nutritional security.